Comparative kinesiology of the human body : normal and pathological conditions - Angin, Salih; Simsek, Ibrahim Engin (Elsevier, Academic Press, an Imprint of Elsevier, 2020)
"Comparative Kinesiology of the Human Body: Normal and Pathological Conditions covers changes in musculoskeletal, neurological and cardiopulmonary systems that, when combined, are the three pillars of human movement. It examines the causes, processes, consequences and contexts of physical activity from different perspectives and life stages, from early childhood to the elderly. The book explains how purposeful movement of the human body is affected by pathological conditions related to any of these major systems. Coverage also includes external and internal factors that affect human growth patterns and development through the lifespan (embryo, child, adult and geriatrics). This book is the perfect reference for researchers in kinesiology, but it is also ideal for clinicians and students involved in rehabilitation practices. Includes in-depth coverage of the mechanical behavior of the embryo as one of the major determinants of human movement throughout the lifecycle. Provides a comparison of human movement between normal and pathological conditions. Addresses each body region in functional and dysfunctional kinesiological terms."--Publisher